Aircraft noise, like heat stress, causes cognitive impairments via similar mechanisms in male mice. (July 2021) - Sun, Gang; Lin, Xiaojing; Yi, Xueqing; Zhang, Peng; Liu, Ruoxu; Fu, Bo; Sun, Yating; Li, Jing; Jiao, Shuxin; Tian, Tian; Xu, Xiao-Ming; Tseng, Kuang-Wen; et al.
Abstract: To our knowledge, little evidence is available about effects of aircraft noise (AN), a non-chemical stressor, on cognitive function. Again, it is unknown whether or not the heat stress (HS)-induced cognitive deficits can be exacerbated by AN. The adult male mice were assigned to four groups: group 1 mice exposed to non-HS (24–26 °C 2 h daily for 4 consecutive days) and white noise (WN) (2 h daily for 4 consecutive days), group 2 mice exposed to WN and HS (32–34 °C 2 h daily for 4 consecutive days), group 3 mice exposed to AN and non-HS (2 h daily for 4 consecutive days) and group 4 mice exposed to AN and HS (2 h daily for consecutive 4 days). Cognitive function were determined by passive avoidance, Y-maze, Morris water maze, and novel object recognition tests. Gut barrier and blood-brain-barrier (BBB) permeability, upload of lipopolysaccharide (LPS) translocation, systemic and central inflammation, and stress reactions were examined. Heat stressed mice displayed both increased stress reactions and learning and memory loss. Heat stress also caused gut barrier hyperpermeability, increased upload of LPS translocation, systemic inflammation, BBB disruption and hippocampal neuroinflammation. Aircraft noise stressed mice did not display systemic inflammation but caused gut barrier hyperpermeability, increased upload of LPS translocation, increased stress reactions, BBB disruption, hippocampal neuroinflammation and cognitive deficits. Aircraft noise exposure further exacerbated the heat stress-induced cognitive deficits and its complications. Our data suggest that AN, like HS, causes cognitive impairments via similar mechanisms in male mice. Graphical abstract: Image 1 Highlights: Heat or aircraft noise induced learning and memory loss in mice. Heat-induced cognitive deficits can be potentiated by aircraft noise. Heat or aircraft noise induced gut barrier and blood-brain-barrier disruption and neuroinflammation. Hypothalamic-pituitary-adrenal axis responses were stimulated by heat or aircraft noise.